Analysis of The Impact of Work Motivation, Work Environment and Career Development on Employee Loyalty Through Job Satisfaction - Gawarudin, Gawarudin; Supratikta, Hadi; Taryo, Taswanda (Journal of Investment Development, Economics and Accounting, 2025)
This study aims to analyze the influence of work motivation, work environment, and career development on employee loyalty through job satisfaction as an intervening variable for employees at the Ministry of Religious Affairs of the Republic of Indonesia. The research method used is a quantitative method with a survey approach through the distribution of questionnaires using a Likert scale. The sampling technique used the Slovin formula with a total of 168 employees as respondents. Data analysis was carried out using the Structural Equation Modeling (SEM) method with the Partial Least Square (PLS) approach through the SmartPLS application The results of the study indicate that work motivation has a positive and significant effect on job satisfaction. The work environment has a positive and significant effect on job satisfaction. Career development also has a positive and significant effect on job satisfaction. Furthermore, work motivation has a positive and significant effect on employee loyalty. The work environment has a positive and significant effect on employee loyalty. Career development has a positive and significant effect on employee loyalty. Job satisfaction also has a positive and significant effect on employee loyalty. In addition, job satisfaction has been proven to be able to mediate the relationship between work motivation, work environment, and career development on employee loyalty.